Development of Head-Loss Evaluation Application Using JAVA for Drip Irrigation System - , Amarjyoti Khound; , Kuldeep Deka; , Shadad Md. Khayer; , Manas Jyoti Bharali; , Arunjyoti Sonowal; , Sudipto Sarkar (Archives of Current Research International, 2024)
Drip irrigation is considered as one of the most efficient irrigation methods used in agricultural field. This method of irrigation is suitable not only in saving water as well as application of fertilizer can also be done very precisely at the crop root zone through fertigation. The drip irrigation set up is a micro irrigation process and it consist of pump, pipe network (Main line, sub main line and laterals), filter unit, drippers, valves, end-cap etc. One model application was developed to introduce with drip irrigation system which will help in efficient water application and used in field to increase the yield of crop the model is developed using java programming language to estimate the major head loss, minor head loss and the total head loss of sub-main and laterals of drip irrigation and it contain two types of calculators. One kind of the calculator is to calculate the head loss when laterals emerged in one side from subs main line and another is to calculate the head loss when laterals are emerged in both sides from the sub-main line in drip irrigation system. Due to head loss when water flow through pipes, there is reduction of total energy occurs and thus uniformity of drip irrigation system is affected. It further affects the flow rate and thus precision of drip system is also reduced due to head loss.